THE EXECUTORIAL FORCE OF RULING OF ADMINISTRATIVE COURT AND THE IMPLICATIONS IN PRACTICE - Gatot Dwi Hendro Wibowo, Firzhal Arzhi Jiwantara & (Jurnal IUS, 2014)
This thesis entitled force executorial administrative court ruling and the implications in practice, discusses the mechanism of execution of the decision of the Administrative Court, the obstacles in the process of execution of the decision of the Administrative Court and the efforts that are made to the administrative court ruling that is not carried by the official / TUN Agency . This type of research is normative and assisted legal research / materials reinforced with empirical law in order to simplify and refine the analysis . The approach used is legislation approach , conceptual approach , approach cases , comparative approach . So that research results can be drawn that the mechanism of execution of court decisions TUN namely : Decision inkracht , after 60 working days the defendant did not perform its obligations , the decision has no legal force again and turns 90 working days of the obligation is not performed , the plaintiff filed a petition to the President of the Court order the court ordered defendant to implement the decision of the court , the defendant is not willing to implement the decision inkracht forceful measures imposed in the form of payment of a sum of money and forced or administrative sanctions and announced in local print media by him, since non-compliance of the court and the chairman shall submit to the President as the highest authority for TUN ordered officials to implement the courtâs decision . So there was a bottleneck in the execution of the ruling Justice TUN namely : Verdict Amar , execution barriers TUN official verdict is due to the position of Regional Chief Political Officer , execution barriers TUN official verdict caused the accused are officials who received the delegation of authority false , barriers of understanding TUN officials the State âs theory of law and AAUPB , technical barriers , barriers juridical ; Barriers related to legal principles , barriers in terms of the limited authority of judges , Barriers due to changes in the system of regional autonomy , Barriers due to noncompliance TUN officials and effort to do the administrative court ruling are not carried by the official / TUN Agency as criminal Attempts by the police to file a criminal report with the basic law 216 of the Criminal Code and civil efforts filed a lawsuit in state court using Article 1365 of the Civil Code as the basis for a lawsuit .Keywords : executorial power , Mechanisms , Barriers and Efforts .